Color-selective numerosity adaptation depends on the automatic categorization of colored information - Grasso, Paolo A.; Anobile, Giovanni; Gurioli, Massimo; Cicchini, Guido M.; Arrighi, Roberto (iScience, 2025)
Numerosity perception is subject to adaptation, but this effect is greatly reduced when adaptor and test differ in color. This color-selectivity has been interpreted as evidence of automatic categorization of color-defined numerical information. However, some argue it instead demonstrates the non-numerical nature of numerosity adaptation. According to this idea numerosity adaptation is a byproduct of low-level filtering of spatial and chromatic information. Here, we contrasted these two perspectives by probing numerosity adaptation and its selectivity to color after equating stimuli in terms of their probability to be filtered out and by directly testing the role of categorization mechanisms in the genesis of color-selective adaptation behaviors. Our results confirm that numerosity adaptation does not depend on the filtering out of visual information and suggest that its selectivity for color genuinely reflects the visual system’s ability to automatically parse between categories when these are defined by salient visual attributes like color. [Display omitted] •The numerical system automatically parses items in color-defined categories•Visual numerosity adaptation is sensitive to the color of the items•Color-selective numerosity adaptation is not a consequence of local color change Neuroscience; Psychology